China Buys the World Analyzing China's Overseas Investments - Collier, Andrew (Springer Singapore, 2018)
This book discusses the strategies that will define China's overseas expansion in the coming years. China is spending billions of dollars acquiring overseas companies and assets, from the Chicago Mercantile Exchange to the Hinkley Point nuclear station. Will this corporate buying binge continue? In this book, Collier argues that state control will occur only among certain strategically key acquisitions while many of the corporate acquisitions will be done by smaller, private firms. However, China's rising debt load may restrict the ability of many firms to obtain capital, including from China's shadow banking sector. A key to understanding China's strategy is to look at how the state intervenes in private business. Collier ably brings clarity to the "gray area" between state and private economic activity in this complex landscape. As the West faces China's growing investments abroad, this book will be required reading for executives and decision makers, journalists, and policy makers.